An integrated approach to near miss analysis combining AcciMap and Network Analysis. (October 2020) - Brian Thoroman, M.S.; Salmon, Paul
Highlights: We analysed led outdoor activity near miss incidents to identify protective factors and relationships. AcciMap and network analysis were integrated to analyse networks of protective factors. An integrated approach provides a richer and more comprehensive analysis. Abstract: Contemporary safety philosophies, such as Safety II, promote the importance of understanding effective work practices as well as those leading to adverse events. Despite this, little safety research has focussed on identifying and representing these protective practices in incident analysis. This study combined AcciMap and network analysis methods to identify and evaluate the system-wide protective practices occurring within a set of led outdoor activity domain near miss incidents. The analysis was based on subject matter expert surveys and interviews regarding near miss incidents. The findings revealed a large set of interrelated protective factors. These factors were about communication, policy and procedure, individual and organisational behavioural influences, and environmental conditions across the sociotechnical system. It is argued that network analysis should be combined with AcciMap in future incident analyses.